HPV-related HNC – new challenge and hope for head and neck cancer subjects - Szyfter, Krzysztof; Kiwerska, Katarzyna; Wierzbicka, Małgorzata (Journal of Medical Science, 2018)
In recent years there are observed substantial changes in epidemiology of head and neck cancer. An incidence of laryngeal cancer is declining as a consequence of decreased tobacco smoking. Contrary, oropharyngeal cancer associated with HPV infection transmitted on sexual way is becoming much more frequent. The latter one is characterized with a better prognosis that most likely does not require intensive therapy. De-escalation of therapy in case of HPV-associated tumor is a matter of current studies.